2016
DOI: 10.1007/s11060-016-2062-8
|View full text |Cite
|
Sign up to set email alerts
|

In vivo multiphoton tomography and fluorescence lifetime imaging of human brain tumor tissue

Abstract: High resolution multiphoton tomography and fluorescence lifetime imaging differentiates glioma from adjacent brain in native tissue samples ex vivo. Presently, multiphoton tomography is applied in clinical dermatology and experimentally. We here present the first application of multiphoton and fluorescence lifetime imaging for in vivo imaging on humans during a neurosurgical procedure. We used a MPTflex™ Multiphoton Laser Tomograph (JenLab, Germany). We examined cultured glioma cells in an orthotopic mouse tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 34 publications
1
62
0
1
Order By: Relevance
“…at the cellular and subcellular levels without tissue treatment or staining to identify glioma tissue, 33,34 as shown in Fig. 6.…”
Section: Brain Diseasesmentioning
confidence: 99%
“…at the cellular and subcellular levels without tissue treatment or staining to identify glioma tissue, 33,34 as shown in Fig. 6.…”
Section: Brain Diseasesmentioning
confidence: 99%
“…Optical bioimaging techniques are most promising in this regard [9], where optical coherence tomography (OCT) [10] and multiphoton microscopy/tomography [11] are capable of visualizing cyto-and myelo-architectonics of the brain.…”
Section: сLinical Medicinementioning
confidence: 99%
“…There is equipment for two-photon microscopy and FlIM, approved for application in clinic, such as MPTflex and DermaInspect systems produced by Jenlab (Germany) [3,96,97].…”
Section: Nadh and Fad Fluorescence Lifetime In Energy Metabolism Evalmentioning
confidence: 99%
“…Thus, NADH lifetime has proved to be considerably shorter in melanoma cells than in those of basalioma and this can serve as a criterion for differential diagnosis [97]. The first study has shown FLIM applicability for evaluating resection borders during neurosurgical intervention on brain tumor in vivo [96]. FlIM spectroscopy has been used in patients with head and neck tumors to reveal that tumor tissue cells have shorter NADH fluorescence lifetime as compared to the surrounding healthy tissue [108][109][110], which suggests their glycolytic status.…”
Section: Nadh and Fad Fluorescence Lifetime In Energy Metabolism Evalmentioning
confidence: 99%